2012
DOI: 10.1136/bjophthalmol-2011-301227
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, clinical features and treatment outcome of microsporidial keratoconjunctivitis

Abstract: Microsporidial keratoconjunctivitis is common in India. It is seasonal, can occur in healthy individuals and can be diagnosed using simple microbiological methods. Treatment outcome is generally satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 15 publications
3
46
1
Order By: Relevance
“…19,26 Recently a study showed that 11.4% of patients with microsporidial keratoconjunctivitis have concomitant adenoviral infection. 27 Specific PCR for adenovirus and enterovirus is negative for all of our specimens.…”
Section: Discussionmentioning
confidence: 99%
“…19,26 Recently a study showed that 11.4% of patients with microsporidial keratoconjunctivitis have concomitant adenoviral infection. 27 Specific PCR for adenovirus and enterovirus is negative for all of our specimens.…”
Section: Discussionmentioning
confidence: 99%
“…45 Microsporidial keratitis is a rare cause of microbial keratitis in immunocompromized patients but it is becoming more frequent, even in immunocompetent patients, due to the increased use of steroids. [51][52][53] It is frequently misdiagnosed, which may result in its progression deeply into the stroma, making corneal transplantation the only choice. 54 IVCM was found to be promising, rapid, non-invasive, with high resolution for identifying the spores of microsporidia, and it is also useful in monitoring the treatment effect and identifying recurrence of the keratitis.…”
Section: Infectious Keratitismentioning
confidence: 99%
“…Keratitis due to Candida , on the other hand, often occurs in patients who are immunosuppressed or in eyes with a poor ocular surface. Another fungal organism that is emerging as a cause of fungal keratitis in tropical Asian countries is microsporidia 30 32. Risk factors for microsporidia include soil exposure, contact lens wear and topical steroid use.…”
Section: Corneal Infections In the 21st Centurymentioning
confidence: 99%